Upaya Pengenalan Kearifan Lokal Pada Anak Usia Dini Melalui Karya Wisata Dieng Wonosobo - Rohana Makrifah; Hidayatu Munawaroh; Yulia Fatimah; Nikmatul Chasanah; Frisca Adina Nur Hana Halatul Baiti; Firma Zulha Lutfiana (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2023)
This study used the observation method by inviting students to visit a place objects direcly to provide learning experiences that are not obtained inside class. In addition to the learning experience students can also get to know local tourism wisdom in their area learning with this method can be done by carrying out visits to tours dieng wonosobo such as candi dieng, kawah sikidang, telag-telaga dieng and many more again. Through this activity, children can see, recognize, and abserve direcly visited abects. Apart fromthat, by having a field trip, children will again the opportunity to get to know local wisdom in the area and grow interest in thing, increasing vocabulary, increasing knowledge and expanding his insight.